2013
DOI: 10.1016/j.ijsu.2013.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of intra-abdominal coagulopathic hemorrhage after living donor liver transplantation

Abstract: Prolonged cold ischemia time is associated with postoperative intra-abdominal coagulopathic hemorrhage in patients after LDLT. It is, therefore, necessary to shorten the cold ischemia time in order to reduce the risk of postoperative intra-abdominal hemorrhage due to coagulopathic causes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The A2ALL Consortium reported that 7% of patients who underwent LDLT experienced intra-abdominal bleeding [ 18 ]. Another report showed that 18 (15.3%) developed intra-abdominal hemorrhage in 118 adult LDLT patients [ 19 ]. Although the incidence and mortality rate of bleeding have not been precisely determined, arterial bleeding after liver transplantation has sporadically been reported to be an obvious cause of death [ 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The A2ALL Consortium reported that 7% of patients who underwent LDLT experienced intra-abdominal bleeding [ 18 ]. Another report showed that 18 (15.3%) developed intra-abdominal hemorrhage in 118 adult LDLT patients [ 19 ]. Although the incidence and mortality rate of bleeding have not been precisely determined, arterial bleeding after liver transplantation has sporadically been reported to be an obvious cause of death [ 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…2,9,[12][13][14][15][16] Transient liver dysfunction after liver transplant can potentially cause bleeding , thereby increasing the chance of coagulopathic hemorrhage. Our data show that patients who developed coagulopathic-related hemorrhage had significantly lower preoperative platelet counts, a longer cold ischemia time, and greater estimated blood loss than patients with noncoagulopathic-related hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Of 161 patients included, 32 developed postoperative hemorrhage. Postoperative hemorrhage was defined as persistent drainage of blood from drainage tubes in association with a hemoglobin drop ≥ 2 g/dL 9 or packed red blood cell transfusion with or without fresh frozen plasma (FFP) transfusion, due to a decrease in hemoglobin concentration to < 7 g/dL. Indication for blood transfusion was massive hemorrhage (> 1500 mL) within 24 to 48 hours after surgery.…”
Section: Patients and Definitions Of Hemorrhage After Livingdonor LIVmentioning
confidence: 99%